KAJIAN ETNOLINGUISTIK PADA ISTILAH PERTANIAN PADI DI KABUPATEN INDRAMAYU JAWA BARAT - Emha, Ratna Juwitasari; Fatinova, Dede; Hardiansyah, Yan (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Language is a cultural creation that can be reflected in the variety of verbal expressions or lexicon spoken by a group of people, as is the case with the people of Indramayu district, especially paddy farmers. This research aims to describe the agricultural lexicon category and describe the meaning of the paddy farming lexicon in Indramayu district West Java. The data in this study is the Indramayu dialect of Javanese language lexicon used by farmers in activities in the field of paddy farming. The theory used in this research is Ethnolinguistics. The method used in this research is descriptive qualitative. The results of this study found that the lexicon in paddy farming in Indramayu district is divided into three categories: nouns, verbs, and adjectives. Meanwhile, in terms of lexical meaning, there are five general classifications were found, the process of planting paddy, planting period of paddy, tools used in paddy farming activities, condition of paddy seeds, and parts of paddy fields.